2012
DOI: 10.3324/haematol.2012.073189
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary relapse of acute myeloid leukemia following allogeneic hematopoietic stem cell transplantation: incidence, risk factors and outcomes

Abstract: Articleshaematologica | 2013; 98 (2) 179 IntroductionAllogeneic hematopoietic stem cell transplantation (HSCT) is increasingly used as a potentially curative treatment for acute myeloid leukemia (AML).1 However post-HSCT relapse remains an important cause of treatment failure with relapse rates ranging from 30% to 70%, 2-5 depending on a number of factors such as disease status at the time of transplantation, donor source, conditioning regimen, and T-cell content of the graft. 4,6 Extramedullary relapses are k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 23 publications
5
78
5
Order By: Relevance
“…In fact, disease relapse is a relatively frequent event, ranging from 30% to 70%, and is dependent on the several factors including disease status at the time of transplantation, donor source and conditioning regimen (50)(51)(52). Recently, a study from Elmaagacli et al has shown that CMV reactivation was associated with reduced risk of relapse in patients with acute myeloid leukemia (53) and actually, these results were corroborated by a few authors that describe similar evidences (26,42,54).…”
Section: Kinetics Of CMV Infectionmentioning
confidence: 54%
“…In fact, disease relapse is a relatively frequent event, ranging from 30% to 70%, and is dependent on the several factors including disease status at the time of transplantation, donor source and conditioning regimen (50)(51)(52). Recently, a study from Elmaagacli et al has shown that CMV reactivation was associated with reduced risk of relapse in patients with acute myeloid leukemia (53) and actually, these results were corroborated by a few authors that describe similar evidences (26,42,54).…”
Section: Kinetics Of CMV Infectionmentioning
confidence: 54%
“…Furthermore, HSCT not only is not an effective procedure for EML, but it can also increase the risk of EML relapse in AML patients. [71] Studies reviewed in this article suggest that cases of AML that have blasts with relatively specific characteristics have a highrisk for non-hematopoietic tissue infiltration. These features may be very helpful in distinguishing patients susceptible to EMI.…”
Section: Resultsmentioning
confidence: 99%
“…This strategy, however, may not be useful for predicting extramedullary relapse, which may not be reliably detected with bone marrow monitoring. (21, 26, 30) Six patients in our study presented with extramedullary relapse as the first manifestation of disease recurrence without prior marrow disease involvement.…”
Section: Discussionmentioning
confidence: 85%